The Correlation Between Genre of Texts and Students’ Reading Comprehension in Arabic Lenguage of the Eight Class of MTs Ummul Quro Pamekasan - Mansyur, M (Dzihni: Jurnal Pendidikan Bahasa Arab, Linguistik dan Kajian Literatur Arab, 2023)
This study focused on the topic, some problems of study have been formulated. They are: Is there any correlation between the genre of texts and students’ reading comprehension in Arabic language of the eight class of MTs Ummul Quro Pamekasan? And How significantthe correlation between the genre of texts and students’ reading comprehension in Arabic language of the eight class of MTs Ummul Quro Pamekasan. This research applies quantitative approach because the data will be studied is in the form of numerical data. The population of this study is the students in eight class of MTs Ummul Quro Pamekasan. There are 4 classes with about 116 students in total. From the results of the research conducted, it can be concluded that there is an any correlation between the genre of texts with students’ reading comprehension in Arabic language of the eight class of MTs Ummul Quro Pamekasan. With a "r_xy" = 0.94, it is greater than the "r" table product moment both at 95% intervals and at 99% intervals where N = 20is 0.44 and 0.56. After researchers have consulted with the level of interpretation, it there significant the correlation between the genre of texts with students’ reading comprehension in Arabic language of the eight class of MTs Ummul Quro Pamekasan with very strong interpretation.